The influence of alternative pathways of respiration that utilize branched‐chain amino acids following water shortage in Arabidopsis - Pires, Marcel V.; Pereira Júnior, Adilson A.; Medeiros, David B.; Daloso, Danilo M.; Pham, Phuong Anh; Barros, Kallyne A.; Engqvist, Martin K. M.; Florian, Alexandra; Krahnert, Ina; Maurino, Veronica G.; Araújo, Wagner L.; Fernie, Alisdair R. (Plant, Cell and Environment, 2015)
During dark‐induced senescence isovaleryl‐CoA dehydrogenase (IVDH) and D‐2‐hydroxyglutarate dehydrogenase (D‐2HGDH) act as alternate electron donors to the ubiquinol pool via the electron‐transfer flavoprotein/electron‐transfer flavoprotein:ubiquinone oxidoreductase (ETF/ETFQO) pathway. However, the role of this pathway in response to other stresses still remains unclear. Here, we demonstrated that this alternative pathway is associated with tolerance to drought in Arabidopsis. In comparison with wild type (WT) and lines overexpressing D‐2GHDH, loss‐of‐function etfqo‐1, d2hgdh‐2 and ivdh‐1 mutants displayed compromised respiration rates and were more sensitive to drought. Our results demonstrated that an operational ETF/ETFQO pathway is associated with plants' ability to withstand drought and to recover growth once water becomes replete. Drought‐induced metabolic reprogramming resulted in an increase in tricarboxylic acid (TCA) cycle intermediates and total amino acid levels, as well as decreases in protein, starch and nitrate contents. The enhanced levels of the branched‐chain amino acids in loss‐of‐function mutants appear to be related to their increased utilization as substrates for the TCA cycle under water stress. Our results thus show that mitochondrial metabolism is highly active during drought stress responses and provide support for a role of alternative respiratory pathways within this response.
Keywords: Branched-chain amino acids; Drought; ETF/ ETFQO pathway; Metabolomics; Respiration; Tricarboxylic acid cycle